A physical limitation of the Wigner "distribution" function in molecular transport - Bâldea, Ioan; Köppel, Horst (Physics letters, 2012)
We present an example revealing that the sign of the "momentum" P of the Wigner "distribution" function f(q,P) is not necessarily associated with the direction of motion in the real world. This aspect, which is not related to the well-known limitation of the Wigner function that traces back to the Heisenberg's uncertainty principle, is particularly relevant in transport studies, wherein it is helpful to distinguish between electrons flowing from electrodes into devices and vice versa.
Available online 29 March 2012
Gesehen am 03.08.2018